114k views
2 votes
6x – 2y = 10 2x + 3y = 51 Solving the first equation above for y gives

1 Answer

2 votes

Answer with Step-by-step explanation:

6x – 2y = 10

2x + 3y = 51

Solving the first equation above for y:

6x-2y=10

⇒ 2y=6x-10

dividing both sides by 2

y=3x-5

Putting value of y in second equation

2x + 3(3x-5) = 51

2x+9x-15=51

11x=51+15

11x=66

⇒ x=6

y=3×6-5

=18-5

= 13

Hence, solution is: x=6 and y=13

and Solving the first equation above for y gives: y=3x-5

User CafeHey
by
6.2k points